Bilateral Intracranial Vertebral Artery Stenosis Presenting as Recurrent Prolonged Presyncopal Episodes. (1st September 2015) - Sundar, Banu; Moonis, Majaz; Wakhloo, Ajay; Puri, Ajit
Abstract : Amongst various mechanisms of presyncopal events, posterior circulation disease needs to be considered. This particular mechanism has been underrecognized. We describe a case of a 76-year-old patient with recurrent posterior circulation TIAs, presenting as recurrent prolonged presyncopal events.